2014
DOI: 10.4103/1596-3519.134383
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward elimination of malaria in Nigeria: Uptake of artemisinin-based combination therapies for the treatment of malaria in households in Benin City

Abstract: Ten years after the historic Abuja meeting, only 5% of households in Benin City used ACTs for the treatment of malaria, sourcing medicines chiefly from patent medicine stores and private hospitals. Fathers' level of education was significantly associated with ACT use. Interventions to eliminate malaria from Nigeria should mainstream the men folk and health care providers outside government hospitals, in line with the Nigerian reality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…Six studies [18,20,21,25,26,28] reported a statistically significant relationship between higher educational level and adherence; four studies [19,24,27,29] reported no statistically significant relationship between the variables.…”
Section: Educational Level and Antimalarial Drug Use Behaviourmentioning
confidence: 99%
See 4 more Smart Citations
“…Six studies [18,20,21,25,26,28] reported a statistically significant relationship between higher educational level and adherence; four studies [19,24,27,29] reported no statistically significant relationship between the variables.…”
Section: Educational Level and Antimalarial Drug Use Behaviourmentioning
confidence: 99%
“…(P <0.001) [26] No association between educational level and adherence/non-adherence [19] The adjusted odds of completed treatment for those who has finished primary school was 1.68 times that of patients who has not (95% CI: 1.20, 2.36; P=0.003) [28] No significant for mothers' attainment of tertiary (or higher) education and the use of ACTs (OR 0.905, CI0.195-4.198; P=0.898) [25] There was a statistically significant association between fathers' attainment of tertiary (higher education) and use of ACTs, when compared to fathers who had not attained this level of education (OR 0.054, CI 0.006-0.510; P=0.011) [25] Adherence and income P=0.003; OR 0.340; 95% CI, 0.167-0.694. higher income level (Ksh >9000 (i.e., >GBP 66 monthly) was associated with ACT adherence [20] [14,20,2 7,31] P=0.034 with participants of higher income salary showing correct dosage of drugs [31] Initiation of home treatment was higher in the poorer households. 25% of the poorest will use home treatment first as against 14% in wealthiest SE category [14] In addition, household monthly income significantly influenced dosage of the drugs used (P=0.034) primarily due to the fact that higher proportions of respondents with an income salary of KShs.…”
Section: Expected Outcome Unexpected Outcome Studiesmentioning
confidence: 99%
See 3 more Smart Citations